2018
DOI: 10.4236/aces.2018.82003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models for Drying Techniques—Food Materials

Abstract: Drying operations can help in reducing the moisture content of food materials for avoidance of microbial growth and deterioration, for shelf life elongation, to minimize packaging and improving storage for easy transportation. Thin-layer drying of materials is necessary to understand the fundamental transport mechanism and a prerequisite to successfully simulate or scale up the whole process for optimization or control of the operating conditions. Researchers have shown that to rely solely on experimental dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 76 publications
3
64
0
5
Order By: Relevance
“…The drying kinetics was modelled in this study to understand the transport mechanism, simulate or scale up the entire optimisation process and control the operating conditions [31]. Therefore, the drying kinetics of M. koenigii leaves dried with CD, MVD, and CPD-MVFD at all drying conditions was determined based on the mass loss throughout the drying process.…”
Section: Modelling Of Drying Kineticsmentioning
confidence: 99%
“…The drying kinetics was modelled in this study to understand the transport mechanism, simulate or scale up the entire optimisation process and control the operating conditions [31]. Therefore, the drying kinetics of M. koenigii leaves dried with CD, MVD, and CPD-MVFD at all drying conditions was determined based on the mass loss throughout the drying process.…”
Section: Modelling Of Drying Kineticsmentioning
confidence: 99%
“…The following statistical measures were used in determining the goodness of fit for the model [2,12,39]: For the experiment, the experimental moisture content data were used to determine the moisture ratio. Thus, it was observed that Moisture Ratio (MR) depends directly on the mass (as shown in Figure 1) and inversely on time (as shown in Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Drying operations had been applied for the reduction of moisture content in food materials for the prevention of microbial growth and deterioration, for shelf life elongation, to minimize packaging and improving storage for easy transportation. Although there are many ways in which drying can be achieved, the choice of a method depends on the material and the sanitary measures [1,2]. Fresh sweet potatoes are highly perishable due to their high moisture content and their availability is seasonal, so in some countries they are processed into various products by drying [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya, data kadar air digunakan untuk menghitung nilai mositure ratio yang digunakan untuk mengkaji kinetika pengeringan busa ampas seduhan teh. Pada dasarnya, persamaan kinetika pengeringan pada model pengeringan lapis tipis diklasifikasikan menjadi tiga kategori yakni: (i) teoritis, (ii) semi teoritis dan (iii) empiris (Inyang et al, 2018). Pada umumnya, model teoritis biasanya diturunkan dari hukum Fick kedua (Fisk's second law).…”
Section: Metodologiunclassified